2010
DOI: 10.1007/s00223-010-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and Bone Mineral Density in Pre- and Postmenopausal Women in Korea

Abstract: Although it has been hypothesized that an atherogenic lipid profile might be associated with lower bone mineral density (BMD), the previous results are controversial. We investigated the association between lipid profile and BMD in premenopausal and postmenopausal women in a large Korean population. This study considered 10,402 women who underwent measurements of lipid profile and BMD from October 2003 to October 2005 at Healthcare System Gangnam Center, Seoul National University Hospital. Participants with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 22 publications
5
53
1
2
Order By: Relevance
“…Another study by Samelson et al in 2004 also reported that total cholesterol levels did not have effect on osteoporosis occurrence in both genders [27]. Our findings are also consistent with that published by Jeong et al in 2012 who found no relationship between total cholesterol, LDL and BMD in pre and postmenopausal Korean women, but they found positive relation between HDL and BMD of lumbar spine only in postmenopausal women [29]. However, our results disagree with studies that showed negative or positive relations between lipids and BMD [31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study by Samelson et al in 2004 also reported that total cholesterol levels did not have effect on osteoporosis occurrence in both genders [27]. Our findings are also consistent with that published by Jeong et al in 2012 who found no relationship between total cholesterol, LDL and BMD in pre and postmenopausal Korean women, but they found positive relation between HDL and BMD of lumbar spine only in postmenopausal women [29]. However, our results disagree with studies that showed negative or positive relations between lipids and BMD [31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 92%
“…While some studies showed no effect of dislipidemia on BMD [27][28][29][30], others reported that there is either a negative [31][32][33][34][35] or a positive effect [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, plasma LDL-C and highdensity lipoprotein cholesterol (HDL-C) levels have been shown to be inversely and positively correlated with BMD in both men and women, respectively [5,6] . However, in some studies, serum triglyceride and HDL cholesterol were found to be correlated with BMD, but no relationship was seen between either total cholesterol or LDL and BMD [7,8] . D'Amelio et al showed that HDL was significantly higher in osteoporotic patients than in controls and the risk of osteoporosis was significantly higher in women with high HDL [9] .…”
Section: Introductionmentioning
confidence: 95%
“…Total cholesterol and LDL-C levels were similarly increased in both pre and postmenopausal obese women compared to controls. Contrary to some other studies, there were no significant differences between lipid profiles of pre and postmenopausal obese women [20][21]. Judith et al showed marked endothelial dysfunction with an increase in LDL cholesterol and a decrease in flow-mediated-dilatation (FMD) within months of estrogen withdrawal [2].…”
Section: Discussionmentioning
confidence: 75%
“…All supernatants which were obtained from every patient serum had same amount of HDL. 200 µl of the isolated LDL solution from a serum pool (adjusted to 50 µg/ml) and 900 µl of test HDL (adjusted to 10 µg/ml cholesterol) were incubated in a tube at [20][21][22][23][24][25] o C and in a dark room for 1 hour. 100 µl of DCFH solution (0.2 mg/ml) was then added to each well and incubated for 2 hours more.…”
Section: The Antiinflammatory Capacity Of Hdlmentioning
confidence: 99%